THE EFFECT OF MOTIVATION AND COMPENSATION ON THE PERFORMANCE OF COFFEE SHOP BARISTA EMPLOYEES IN PALEMBANG CITY - Andreas Natanael (Program Studi Manajemen, Fakultas Bisnis & Akuntansi, Universitas Katolik Musi Charitas, 2025)
Employee performance isn't just about promotions or salary determination. It's also about how companies motivate employees and how they implement efforts to improve learning and performance. The purpose of this study was to simultaneously and partially determine the impact of work motivation and compensation on the performance of barista employees at coffee shops in Palembang. Data were obtained through a survey of coffee shop employees in Palembang. Simultaneous hypothesis testing revealed that work motivation and compensation did not have a significant impact on employee performance. This study suggests that coffee shops in Palembang should pay more attention to their employees, specifically baristas, to foster work enthusiasm, which can ultimately motivate them and improve performance.